Influence of green product innovation, green process innovation, green product competitive advantage on the new green product success: Evidence from SME plastic manufacturers - Cheong, Dennis Kit Mun; Yeoh, Khar Kheng (2017)
The growing environmental concern among consumers has triggered many firms including the small and medium enterprises (SMEs) in the plastic industry to adopt innovative strategies to meet the green requirement.It is argued that these firms can achieve competitive advantage by adapting to changing consumer and societal demands for greater green products and processes.Against this background this study investigated the effects of green product innovation and green process innovation on green new product success of manufacturing SMEs in the plastic industry in Malaysia.The study also examined the mediating role of green product competitive advantage on the relationship between green product innovation and green new product success, and between green process innovation and green new product success.Data were collected from the SME plastic manufacturers registered with the Malaysian Plastic Manufacturers Association (MPMA) and systematic random sampling was employed in selecting them from the sampling frame.A total of 556 self-reported questionnaires were emailed to the respondents and 207 were received, giving a response rate of 37.23 percent.However, only 191 responses were usable for the final analysis. Findings revealed that green product innovation and green process innovation were positively and significantly related to green new product success.Further analysis indicated that green product competitive advantage partially mediated the relationship between green product innovation, green process innovation, and green new product success.The findings of this study contribute mainly to the current literature on green innovation especially in the Malaysian context where similar studies are generally scarce.Moreover the study specifies a strategy on how to improve the green new product success among SMEs in the plastic industry.The study concluded with a discussion of the theoretical and practical implications, the limitations as well as suggestions for future research.